2017
DOI: 10.1007/s11229-017-1544-3
|View full text |Cite
|
Sign up to set email alerts
|

On serendipity in science: discovery at the intersection of chance and wisdom

Abstract: (226 words):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 42 publications
1
62
0
10
Order By: Relevance
“…Makri et al [17] regarded serendipity as a new connection made by integrating unexpectedness and insight. Copeland [18] summarized three interrelated features of serendipity in science. First, serendipity is volatile.…”
Section: Concepts Of Serendipity In Sciencementioning
confidence: 99%
“…Makri et al [17] regarded serendipity as a new connection made by integrating unexpectedness and insight. Copeland [18] summarized three interrelated features of serendipity in science. First, serendipity is volatile.…”
Section: Concepts Of Serendipity In Sciencementioning
confidence: 99%
“…Throughout these years, he constantly trained his vision to detect relevant anomalies, which made him "the perfect eyewitness for this unlikely microbiological contingency […] a receptive observer." (Bennett and Chung 2001, p. 168) What it means to be a skilled observer varies with the context: In this case, it presumes knowledge of the state of the art of the scientific discipline and an idea of what counts as relevant and novel from this perspective (Copeland 2017). McFarlane summarizes Fleming's scientific merits in a similar manner: "If [Fleming] cannot be given the credit for the accidents, he should be granted the keen eye that observed them and the prepared mind that appreciated their interest."…”
Section: The Case Of Alexander Flemingmentioning
confidence: 99%
“…68-69). 6 In this manner, it is suggested that developing certain epistemic skills increases the likelihood of becoming scientifically lucky, such as training certain virtues increases the likelihood of becoming morally lucky (Copeland 2017;McKinnon 2014). In so far as it is up to the agent to deliberately train such skills or accept certain risks when driving negligently, these freely adopted volitions constitute the basis of someone's moral standing (Concepcion 2002, p. 459).…”
Section: Moral Luck and Common Objectionsmentioning
confidence: 99%
See 2 more Smart Citations